Flaw acceptability assessment detected in HSLA steel weld joints - Rak, Inoslav (Kovine zlitine tehnologije, 1999)
The flow size in weld joint can be determined by non destructive examination (NDE). Because of different mateials, and loading as well as because of the possible effect of corrosive environment the question arises how to assess reliably the allowable falw size in different weld joint parts. The presence of flaws is obvious but the possibilities of their revealing are limited and not always posssible. The flaw size and distribution are the essential parameters for the structure capacity of bearing under high loading the weld joint. The larger is the allowable flaw size anticipated, the safer is the welded structure, and the easiest is the detection of the flaw size by NDE methods. Thus for assessing the safety of complex loaded welded structure, machine parts or equipment life time, it is obligatory to consider the requirements of different "Fitness for Purpose" systems. The article presents the possibility of assessing the detected flaw by means of NDE if the material fracture toughness of the area where the fatigue crack tip located is known. The fatigue crack represents the severest discontinuity that can occur in a welded joint. The principles of IIW Guidance on Assessment of The Fitness for Purpose of Welded Structures - IIW/IIS-SST-1157-90 and BS PD 6493 and separately ETM that treats mis-matched weld joints are shown and used.
Keywords: neporušne preiskave; zvarni spoji; napake; lomna žilavost; trdnost